Toxic myopathy in experimentally intoxicated pigs due to consumption of Senna occidentalis pods and seeds - Chileski, Gabriela S. (2018)
The clinical and pathological findings of the experimental poisoning by Senna occidentalis in pigs are described. Six pigs were distributed into two groups, one of which was fed a ration containing 10% pods and seeds of S. occidentalis for 30 days and the other group remained as a control group. The intoxicated animals showed lethargy, ataxia, muscular tremors, emaciation and recumbency. The enzyme creatine phosphokinase increased significantly in pigs intoxicated with S. occidentalis (p<0.05). The histopathology revealed that the intoxicated pigs mainly had degeneration of the muscle fibres and fibrosis in the skeletal muscles. Electron microscopy revealed mitochondrial lesions. The results confirm the myotoxic effect of chronic poisoning by S.occidentalis in pigs.